Aspirin Resistance. (14th April 2009) - Mansour, Khaled; Taher, Ali T.; Musallam, Khaled M.; Alam, Samir
Abstract : The development of adverse cardiovascular events despite aspirin use has established an interest in a possible resistance to the drug. Several definitions have been set and various laboratory testing modalities are available. This has led to a wide range of prevalence reports in different clinical entities. The etiologic mechanism has been related to clinical, genetic, and other miscellaneous factors. The clinical implications of this phenomenon are significant and warrant concern. Management strategies are currently limited to dosing alteration and introduction of other anitplatelet agents. However, these measures have not met the expected efficacy or safety.